An investigation into the impact of the gender policy on journalistic practices at the Times of Zambia newspaper - Mwale, Edna (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
This study investigates the impact of the Times of Zambia gender policy on journalistic practices. The policy was formulated to address issues of representation of women both in news coverage and at an institutional level. In spite of the implementation of the editorial gender policy, no change in gendered representation is evident. As a media practitioner and a Zambian woman concerned with social justice, I set out to investigate the impact of this policy on journalistic practices. The study is informed by a Cultural Studies approach to media studies, specifically drawing on the 'circuit of culture' (du Guy et ai, 1997) and focused on two specific 'moments', namely representation and production. Data was collected using two qualitative methods, namely document analysis and semi-structured in-depth interviews. The document analysis established that this policy is informed by a liberal feminist approach to media and identified the weaknesses in its formulation. The subsequent semi-structured in-depth interviews probed the practices and perceptions of male and female journalists and editors in relation to the degree of change in gendered representation in the news. This study finds that the editorial gender policy at the Times of Zambia has not had any significant impact on the journalistic practices and it probed the reason for this lack of effectiveness. It argues that this can be partially attributed to the orientation of the policy within a liberal feminist paradigm which neglects the internal and external factors that influence the representation of women and men in news production. Further, this position ignores the societal structures and power relations which impact, albeit unintentional, on the treatment of news. Inter-organisational factors such as profit maximisation, political interference, the use of news values and news beats are identified as leading to the exclusion of representations of women in hard news. At an intra-organisational level, lack of importance attached to the policy by senior staff and their attitudes to news production in general have meant that the policy was not enacted or ensured in any meaningful way. The study also established that the patriarchal values that characterise Zambian society influence journalists ' and editors' treatment of news, thus making the implementation of the policy ineffective.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: The Times of Zambia (Zambia); Newspapers -- Zambia Journalism -- Zambia; Mass media -- Social aspects -- Zambia; Women and journalism -- Zambia; Mass media and women; Mass media -- Political aspects -- Zambia; Zambia -- Politics and government